Circuit breakers with uncertainty about the presence of informed agents: I know what you know . . . I think - Lucy F. Ackert; Bryan K. Church; Narayanan Jayaraman (Federal Reserve Bank of Atlanta, 2002)
This study conducts experimental asset markets to examine the effects of circuit breaker rules on market behavior when agents are uncertain about the presence of private information. Our results unequivocally indicate that circuit breakers fail to temper unwarranted price movements in periods without private information. Agents appear to mistakenly infer that others possess private information, causing price to move away from fundamental value. Allocative efficiencies in our markets are high across all regimes. Circuit breakers perform no useful function in our experimental asset markets.
Keywords: 330; Markets; Financial markets; Risk